Import Competition and Internal Migration - Greenland, Andrew; Lopresti, John; McHenry, Peter (The Review of Economics and Statistics, 2019)
We examine the U.S. internal migration response to increased import competition following the granting of Permanent Normal Trade Relations to China in 2001. Using a variety of data sets and empirical approaches, we find that local labor markets most exposed to the policy change experienced a relative reduction in population growth over the following decade. The majority of the effect occurs at a lag of seven to ten years and is most pronounced among young individuals and low-education groups. Such population adjustments should influence the interpretation of evidence in the growing literature on import competition and local labor markets.